2013
DOI: 10.1007/s13105-013-0289-9
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of 17beta-estradiol against ischemia–reperfusion injury and its effect on pacing postconditioning protection to the heart

Abstract: The role of pacing postconditioning (PPC) in the heart protection against ischemia-reperfusion injury is not completely understood. The aim of this study was to investigated if 17-β-estradiol (estrogen, E2), endogenous atrial natriuretic peptide (ANP), endogenous brain natriuretic peptide (BNP), and tumor necrosis factor-alpha (TNF-α) are involved in PPC-mediated protection. Langendorff perfused female Wistar rat hearts were used for this study. Hearts challenged with regional ischemia for 30 min subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Moreover, PPC induced a remarkable reduction in the CK and LDH levels. Although evaluations of hemodynamics have seldom been conducted, the protective effects of PPC were reported by us and other researchers [1,2,30,34]. However, the pathways involved in PPC-mediated protection and the interaction between PPC and body homeostasis have not been completely elucidated.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, PPC induced a remarkable reduction in the CK and LDH levels. Although evaluations of hemodynamics have seldom been conducted, the protective effects of PPC were reported by us and other researchers [1,2,30,34]. However, the pathways involved in PPC-mediated protection and the interaction between PPC and body homeostasis have not been completely elucidated.…”
Section: Discussionmentioning
confidence: 97%
“…Anesthesia was administered to the rats via intraperitoneal injection of sodium pentobarbital (60 mg/kg), and the anticoagulant heparin (a dose of 1000 U/kg body weight) was delivered via the femoral vein. Heart cannulation and perfusion were performed as described previously [1]. Briefly, the isolated heart was retrogradely perfused with freshly prepared KrebsHensleit buffer (117.86 mM NaCl, 5 Oxygenation was performed using a mixture of CO 2 (5 %) and O 2 (95 %) at a pH range of 7.35 to 7.45 and at a temperature of 37.0 ± 0.5°C.…”
Section: Animals and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Premenopausal women have reduced cardiovascular disease and the occurrence increases after menopause 1, 2 . Furthermore, many studies in animal models have reported less hypertrophy and less ischemia-reperfusion (I/R) injury in females compared to males 3, 4 . Additional studies with ovariectomized females have also shown that addition of estrogen reduces hypertrophy and I/R injury 5 (Figure 1 summarize the cardiovascular effects associated with estrogen).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has indicated that opioid receptor agonists can protect diastolic and systolic function following ischemia-reperfusion (19). Kin et al (20) revealed that an opioid receptor agonist had no effect on myocardial diastolic and systolic function prior to ischemia, but that the left ventricular end-diastolic pressure (LVEDP) of the agonist group prior to ischemia increased more slowly and that cardiac spasmodic contraction occurred later than in the control group.…”
Section: A B C Dmentioning
confidence: 99%